Handbook of methods in cultural anthropology - Bernard, H. Russell (Harvey Russell) 1940- (Altamira, 2000)
The "Handbook of Methods in Cultural Anthropology" establishes a benchmark for synthesizing anthropological research practices over the past 100 years. Avoiding the divisive debates over science and humanism, the authors contributing to this important volume draw upon both traditions to define and describe anthropological fieldwork in practice. Authored by 27 of the leaders in the discipline, these chapters provide the reader with comprehensive, contemporary descriptions of the methods that anthropologists use, the logic behind them, and the complex problems that field research with humans entails. In addition to traditional participant observation and related strategies, the "Handbook" examines historical methods, surveys, linguistic methods, comparative research, social intervention, and visual anthropology as ways in which anthropologists seek to understand the world. Related questions of research strategies and designs, ethics, epistemology, and presentation of anthropological results round out the volume. This is an essential reference tool for all academic, professional and graduate-level anthropologists, and will also be of inestimable value to other social researchers who use field methods in their work.